TEMPORAL AND INTRADAY ABUNDANCE VARIATIONS OF BLISTER BEETLE (MYLABRIS PHALERATA) ON GREENGRAM - K. S. PAWAR; S. P. DHAVAN; R. M. WADASKAR (The Bioscan, 2013)
Temporal and intraday abundance variations of blister beetle (Mylabris phalerata) on greengram under regular and late sown condition were recorded at Pulses Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola. The abundance of blister beetle and crop phenology revealed population from bud initiation stage with a peak during flowering and early pod formation stage, clearly indicating its preference for the buds and flowers. Higher abundance of blister beetle adults during pod formation stage can be attributed to second flush of greengram. The beetle population decreased when the crop reached physiological maturity. Correlations of weather parameters with blister beetles abundance revealed that maximum temperature, minimum temperature and bright sunshine hours were significantly correlated in negative manner. Morning relative humidity and evening relative humidity had positive influence on blister beetle abundance. The number of rainy days and rainfall had positive correlation with seasonal abundance of the beetles, though the later being statistically non significant. Strong association of evaporation in negative manner was also evident. Thus, it may be inferred that the blister beetles population had preference for low temperature regime and less bright sunshine hours and more rainy days, indicating positive influence of rainfall. Highest feeding activity of adult blister beetles with orientation to sunlight was recorded during pre noon period whereas, most of the adult blister beetles preferred idleness (avoiding sunlight) post noon period. At dusk, adults preferred to congregate at higher position above crop canopy.